Effect of Chicory-derived Inulin on Abdominal Sensations and Bowel Motor Function. Issue 7 (August 2017) - Azpiroz, Fernando; Molne, Laura; Mendez, Sara; Nieto, Adoración; Manichanh, Chaysavanh; Mego, Marianela; Accarino, Anna; Santos, Javier; Sailer, Manuela; Theis, Stephan; Guarner, Francisco
Abstract : Goal: To determine the effect of a prebiotic chicory-derived inulin-type fructan on the tolerance of intestinal gas. Background: Subjects with gas-related complaints exhibit impaired handling of intestinal gas loads and we hypothesized that inulin would have a beneficial effect. Study: Placebo-controlled, parallel, randomized, double-blind trial. Subjects with abdominal symptoms and reduced tolerance of intestinal gas (selected by a pretest) received either inulin (8 g/d, n=18) or maltodextrin as a placebo (8 g/d, n=18) for 4 weeks. A gas challenge test (4 h jejunal gas infusion at 12 mL/min while measuring abdominal symptoms and gas retention for 3 h) was performed before and at the end of the intervention phase. Gastrointestinal symptoms and bowel habits (using daily questionnaires for 1 wk) and fecal bifidobacteria counts were measured before and at the end of the intervention. Results: Inulin decreased gas retention during the gas challenge test (by 22%; P =0.035 vs. baseline), while the placebo did not, but the intergroup difference was not statistically significant ( P =0.343). Inulin and placebo reduced the perception of abdominal sensations in the gas challenge test to a similar extent (by 52% and 43%, respectively). Participants reported moderate gastrointestinal symptoms and normal bowel habits during baseline examination, and these findings remained unchanged in both groups during the intervention. Inulin led to a higher relative abundance of bifidobacteria counts ( P =0.01 vs. placebo). Conclusions: A daily dose of inulin that promotes bifidobacteria growth and may improve gut function, is well tolerated by subjects with gastrointestinal complaints.